Internalização e externalização de serviços públicos no Rio Grande do Sul: estudo da reversão de contratos - Silva, Daiane Fraga da (Universidade do Vale do Rio dos Sinos, 2023)
Although outsourcing to private provision of public services is common, reversions of these services to public provision are also common. As an empirical source, secondary data was analyzed to explore the hiring dynamics of Municipal Governments, in the municipalities of Rio Grande do Sul. Public data available on the Transparency Portal platforms of the municipalities, the State of Rio Grande do Sul and the Court of Auditors of the State of Rio Grande do Sul were used. In particular, since 2017 the Court has been collecting information regarding municipal and public tenders. their administrative contracts. This provides a solid and broad database in the sample (all municipalities) and temporal (period from 2017 to 2022) dimensions. To then identify which factors are related to the reversal of these externalized contracts in the municipalities of the state of Rio Grande do Sul. Given this, the diagnostic analysis was based on the development of econometric models, with the dependent variable of contract reversal. In its independent variables, in the characteristics of the contracts described by the management and financial variable. Finally, the control variable, with the characteristics of the municipalities specified by population and mesoregion. The research took place in almost 100 municipalities, in a total of 40,670 public service provision contracts, in the analysis of the econometric model, for this research, what was most promising was the robustness model with all its tests, for the interpretation we applied the significance relationships and coefficients, to then know what the implications would be for public service, in each variable. The study shows that there is a low tendency for contract reversal, some of the factors that can lead to this would be the value of the contract, the lower it is, the easier it is to reverse, as well as time, the less time the company has to contract with the municipality, the probability of service reversal is greater.
Keywords: Contrato; Externalização; Internalização; Contract; Externalization; Internalization; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis